Differentials in dietary intake of macro and micronutrients in patients with type 2 diabetes and foot ulcers: Observations from a pilot study. (February 2022) - Reddy, Sandhiya; Anoop, Shajith; Jebasingh, Felix K.; Dasgupta, Riddhi; Joseph, Mini; Saravanan, Bharathi; Volena, Ruth; Mani, Thenmozhi; Somasundaram, Sivaruban; Bhattacharji, Suranjan; Nair, Sukesh C.; Paul, Robin Daniel; et al.
Summary: Background and aim: The dietary profiles of patients with type 2 diabetes mellitus (T2DM) from Southern India have been infrequently studied. We aimed to study the differences in dietary intake of macro and micronutrients in elderly patients of Type 2 diabetes mellitus (T2DM), with and without foot ulcers. Methods: Elderly patients with T2DM and foot ulcers (n = 79; mean age: 60.6 years) and those without foot ulcers ( n = 59; mean age: 55.0 years) were studied. Biochemical evaluation for measures of glycemia, lipids and albumin were done and staging of foot ulcers was done using Wagner's scale. A 24-hour dietary recall was administered to quantify the mean daily intake (MDI) of macro, micronutrients and trace elements from portion sizes of food items consumed and compared to the recommended dietary allowance (RDA) for Indians aged 55 years and above. Results: In patients with T2DM and foot ulcers, the MDI of carbohydrates, fats and phosphorus were significantly higher whereas the MDI of proteins and micronutrients namely zinc, folic acid, iron and carotene were lower than the RDA. Elderly patients with nephropathy and longer duration of T2DM have higher odds of developing foot ulcers, when compared to patients without foot ulcers. Conclusion: Elderly patients with T2DM and foot ulcers were deficient in dietary intake of proteins and micronutrients inclusive of carotene, folic acid, zinc, and Iron. Clinical care, regular monitoring of dietary intake and appropriate correction of nutritional deficiencies will aid in the management of diabetic foot ulcers.